Peran Kepala Sekolah dalam Menata Konsep Manajemen Strategi di MIS Al-Ihsan Kelurahan Siantan Hulu - Nawang Wulan; Samiyah (Jurnal Pendidikan Dasar Islam, 2024)
The role of the school principal is very important in determining the direction and success of educational institutions. This article discusses how school principals can be a driving force in implementing strategic management concepts in schools. With a systematic approach, school principals can ensure the school's vision and mission are achieved effectively. This study also highlights strategic steps that school principals can take in planning, implementing and evaluating strategic management. In addition, this article identifies the main challenges faced in implementing strategic management and offers practical recommendations for increasing the effectiveness of school principals' strategic leadership. By understanding this role in depth, school principals can create an innovative, inclusive and sustainable educational environment.